Inheritance of the main elements of productivity and adaptability parameters in diallelic hybrids of spring soft wheat - L. V. Volkova; O. S. Amunova (Аграрная наука Евро-Северо-Востока)
In the conditions of the Kirov region, there was conducted a comparative study of 20 hybrid populations of F2, F3, F4, created according to a complete diallel scheme, and 5 parent forms of spring soft wheat by the traits of productivity and adaptability. In contrast in terms of heat and moisture supply in 2020–2022 (hydrothermal coefficient 1.07–1.44) in parental forms and hybrids the dominant influence of the genotype on the trait "weight of 1000 grains ", environmental conditions on the trait "number of grains per spike " and "yield" was revealed. In the group of hybrids, an increase in the proportion of "genotype × environment" interaction was noted in all indicators. There was a redefinition of correlations between traits depending on the influence of limiting factors, as well as an annual change in the ranks of hybrid combinations both in terms of average values of traits and in the manifestation of heterosis and depression. The characteristics of the initial varieties and hybrid populations according to the parameters of plasticity and stability are given, the patterns of inheritance of adaptive reactions are studied. The reaction to environmental conditions based on the "number of grains per spike " trait was inherited mainly by an intermediate type, most high-plastic genotypes were obtained with the participation of ʻMargaritaʼ and ʻLiniya 2ʼ cultivares, low-plastic ones with the participation of the Saratovskaya 29 cultivar. The percentage distribution of the type of reaction of the "weight of 1000 grains" trait occurred towards an increase in the number of high–plastic combinations, by the yield – according to the distribution of parent forms. The inclusion of the original ʻKarabalykskaya 98ʼ form in crosses increased the regression coefficient of the "1000 grain weight" trait in hybrids, and the ʻMargaritaʼ cultivar increased the "yield" trait. The high convergence of the average level of traits, the level of heterosis and the values of the plasticity coefficient in hybrid populations, and the relative independence of the indicator "phenotypic stability" (S,%) were revealed. Yield plasticity largely depended on the plasticity of the "number of grains per spike " trait, while the maternal components had a greater influence. As a result of the research, the best combinations have been identified, from which it is preferable to conduct selections for the main elements of productivity and adaptability parameters in the selection of spring soft wheat.